2023
DOI: 10.1186/s12993-023-00205-y
|View full text |Cite
|
Sign up to set email alerts
|

Pristane induced lupus mice as a model for neuropsychiatric lupus (NPSLE)

Abstract: Background The pristane-induced lupus (PIL) model is a useful tool for studying environmental-related systemic lupus erythematosus (SLE). However, neuropsychiatric manifestations in this model have not been investigated in detail. Because neuropsychiatric lupus (NPSLE) is an important complication of SLE, we investigated the neuropsychiatric symptoms in the PIL mouse model to evaluate its suitability for NPSLE studies. Results PIL mice showed olfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…To evaluate the effect of optogenetic stimulation of BF cholinergic neurons on brain pathophysiological changes, we examined cytokine expression, IgG deposition and lipofuscin accumulation in the brain by ELISA and immunofluorescence staining. Consistent with our previous results [ 15 ], PIL mice presented significantly increased expression of brain cytokines, including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1β and IL-10 (Fig. 4 A).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To evaluate the effect of optogenetic stimulation of BF cholinergic neurons on brain pathophysiological changes, we examined cytokine expression, IgG deposition and lipofuscin accumulation in the brain by ELISA and immunofluorescence staining. Consistent with our previous results [ 15 ], PIL mice presented significantly increased expression of brain cytokines, including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1β and IL-10 (Fig. 4 A).…”
Section: Resultssupporting
confidence: 92%
“…The reduction of cytokines may be related to the lessened cytokine entries from peripheral circulation due to the improved BBB leakage, and the reduced local cytokine production following a decreased invasion of inflammatory stimulators. IgG deposition has been observed in the hippocampus of PIL mice [ 17 ], which may result from the impairments of BBB, blood-ventricular barrier and choroid plexus-vascular barrier [ 15 ]. Thus, the reduction of IgG deposition in the choroid plexus and lateral ventricular wall may be attributed to the improved vascular barrier function by BF stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the level of animal models, depressive behavior is spontaneous in MRL/lpr transgenic mice, which is the most common SLE animal model and characterized by the abnormal activation of T and B cells. In addition, pristane-induced lupus mice, which is another useful model for SLE, exhibit a series of neuropsychiatric behavioral deficits and pathological changes in the brain [18]. Furthermore, it was found that the stressinduced metabolic disorder of CD4+ T cells can lead to anxiety-like behavior [19].…”
Section: Introductionmentioning
confidence: 99%